2020
DOI: 10.1136/bcr-2019-233068
|View full text |Cite
|
Sign up to set email alerts
|

Type B lactic acidosis: a rare oncological emergency

Abstract: Type B lactic acidosis is a rare metabolic complication of malignancy, more commonly in haematological malignancies. Due to the lack of formal prospective trials, treatment of lactic acidosis associated with malignancy is based on case reports. Given the poor prognosis, early recognition of type B lactic acidosis and prompt treatment are crucial. We report the first case of type B lactic acidosis in metastatic melanoma, followed by a brief literature review on the proposed pathophysiology and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In contrast, type B lactic acidosis, which is usually associated with normal tissue perfusion, is caused by liver disease, vitamin B1 deficiency, alcoholism, metformin use, and malignancies. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, type B lactic acidosis, which is usually associated with normal tissue perfusion, is caused by liver disease, vitamin B1 deficiency, alcoholism, metformin use, and malignancies. 2 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, type B lactic acidosis, which is usually associated with normal tissue perfusion, is caused by liver disease, vitamin B1 deficiency, alcoholism, metformin use, and malignancies. 2 Type B lactic acidosis is a rare but lifethreatening disease that mainly occurs in patients with hematological malignancies but may also occur with solid tumors. 3 The early detection of type B lactic acidosis is of great significance to its diagnosis, treatment, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Type B lactic acidosis stemming from malignancy is most commonly associated with hematologic malignancies. 10 Multiple theories exist as to why this occurs, including increased pyruvate production, thiamine depletion, or increased rates of glycolysis in tumor cells. 10 As demonstrated in the presented case, identification of type B lactic acidosis is often delayed as type A is far more common and is often ruled out first.…”
Section: Discussionmentioning
confidence: 99%
“…There are few cases of solid tumors associated with lactic acid in the literature. The revision made by Liu et al [ 14 ] showed a set of 50 cases of lactic acidosis associated with solid tumors and 14 cases since 2010. These tumors share common characteristics, and a lot of them were poorly differentiated and had liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other possible explanations for the increase of this metabolite [ 2 ]. Since malignancy may be a treatable cause, it is important to include it in the differential diagnosis [ 3 ]. On the other hand, urinary tract infections are one of the most frequent causes of emergency consultations, and older age is associated with a worse outcome, increasing the risk of sepsis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%